HASIL EVALUASI DIRI SEKOLAH DAN PENENTUAN PRIORITAS REKOMENDASI DALAM MENINGKATAN KUALITAS PENDIDIKAN ISLAM - Putri, Farih Annisa; Damayanti, Husnaya Dwi; Mardiyah, Mardiyah (STAI Sangatta Kutai Timur, 2025)
In the context of Islamic education, evaluation functions as a tool to measure the achievement of learning objectives. One method used in assessing the effectiveness of school performance is School Self-Evaluation (EDS). Optimal implementation of EDS aims to help schools identify problems, adjust educational programs, and improve the quality of the learning process. In order to support the improvement of education quality, schools need to understand and implement the principles of self-evaluation management as a whole. This study uses a qualitative approach with a library research method. EDS/M has an important role in identifying strengths, weaknesses, opportunities, and challenges related to achieving education quality standards, as well as being the basis for preparing the Madrasah Work Plan and Budget (RKAM) or School Work Plan (RKS). Therefore, this article reviews the basic concept of school/madrasah self-evaluation management, the evaluation results obtained, and provides recommendations to encourage the improvement of the quality of Islamic education in the current era.